Concept of happiness / Mahadzir Ismail and Jamilah Laidin - Ismail, Mahadzir; Laidin, Jamilah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Happiness is something that everybody is looking for. While some may be enjoying a happy life day and night, the other may end up living in misery. However, if someone asks what makes you happy which sounds a simple one but finding the answer is not that easy. By its nature, happiness does not have a st raight meaning. It is a multidimensional and cannot be assessed by one single measure (Ng, 2015). The literature shows that happiness became an interesting topic when the Bhutan government decided to make public happiness as an indicator for national progr ess back in 1979. What is more significant step that the Gross National Happiness (GNH) has been included as part of the Bhutan’s constitution in 2008. Since then the GNH had been gaining momentum and got the attention of the United Nations Assembly. In 20 12, the first World Happiness Report was produced and showed the ranking of the countries in term of the level of happiness of the citizens. Now days happiness is increasingly considered the proper measure of social progress and the goal of public policy ( Helliwell, Layard & Sachs, 2017).